Routines to keep healthy during the Coronavirus quarantine period (Barca Innovation Hub, 2020)
How can we keep healthy during isolation? There are a lot of small activities we can do in order to promote salutogenesis. For example, taking deep breaths, practising meditation, exercising, taking a nap, among others…